Adipose-derived stem cells in the treatment of knee osteoarthritis: from extraction methods to the preparation of the transplant (Research, Society and Development, 2022)
Introduction: Recent studies have investigated the use of adipose tissue as source of mesenchymal stem cells in the treatment of knee osteoarthritis in humans. However, there are still several protocols being performed. Objective: Analyze the protocols published in the literature in the last ten years and to investigate how they are being carried out and if they are following the criteria adopted by the International Federation for Adipose Therapeutics and Science (IFATS) and the International Society for Cellular Therapy (ISCT). Methodology: Articles from the PubMed, ScienceDirect and Lilacs database published in January / 2010 until the present time, which were evaluated in order to investigate the use of adipose-derived stem cells in the treatment of knee osteoarthritis. Results: Thirty four articles were evaluated in its entiraty. The abdominal area was the most choosen to do the liposuction, however the quantities of adipose tissue removed and the number of cells transplanted was variable.  It is hightlited the enzimatic digestion of adipose tissue with collagenase as extraction method. Only 14 articles complied all the 3 criteria required to prove the real presence of mesenchymal stem cells in the samples that was transplanted. However, all the articles showed improvement of function and pain. Final considerations: Thus, even the results found are promising, the evidence is still limited in humans and the variability of the methodology makes it difficult to standardize the technique, also its implementation as a reference in the treatment of knee osteoarthritis.